The differences in energy system demands of competitive male tennis play between fast and slow courts - Skorodumova, A.; Baranov, I. (Coaching and Sport Science Review, 2019)
This study investigated the energy system demand differences between matches played on fast courts and on slow courts of highperformance male players. Matches of Grand Slam matches played by Russian players were analysed. External indicators as such in-point playing time as a proportion of total match time were used to conduct the analysis. Data analysis found significant differences in all measured external indicators such as average match playing time, number of points and in-point time. Results also found a significant difference between match motor density (the percentage of total match time that made up effective playing time) for the two surface types, with the slow surface (clay) match motor density being significantly higher than that of the fast surface (grass and hard court), 14.5% and 12.9%, respectively. Subsequent analysis of point length reveals that slow courts had a significantly higher percentage of points that lasted more than 10 seconds whilst fast courts has a higher percentage of points under 10 seconds in length. It can be concluded that due to the length of the points, tennis primarily employs the ATP-PCr energy system for energy use, dipping into the anaerobic lactic acid energy pathways more on clay court matches. Whilst the aerobic pathways are not employed heavily in-point, they are still essential, possibly even more on clay court due to greater taxation on the anaerobic lactic acid pathway, as they provide the basis for ATP re-synthesis between points. This signals toward endurance as a major component of fitness in tennis.